Ketahanan Perbankan Syariah di Indonesia Terhadap Fluktuasi Kondisi Makroekonomi dan Fundamental Saat Pandemi Covid 19 - Purbayati, Radia; Pakpahan, Rosma; Juniwati, Endang Hatma; Rivanda, Agil Krisna (JESI (Jurnal Ekonomi Syariah Indonesia), 2022)
The aims of this study is to examine the business resilience of the Islamic banking in Indonesia, and predicts the recovery of Islamic banking performance due to the shock of the Covid-19 Pandemic. The population in this study was Islamic Commercial Banks. The research focused on all Islamic Banking in Indonesia, period January 2017 to May 2022 as many as 12 Sharia Commercial Banks consisting of 1 bank in the Bank Group based on Core Capital (KBMI) 3, 1 bank is in KBMI 2 and 10 banks are in KBMI 1. The research used a descriptive analysis method of the Islamic banking in Indonesia. The variables tested included the ratio of NPF, CAR, ROA, Asset SIZE and GDPG growth. The analysis tool used VAR/VECM. The results showed that the business resilience of the Islamic banking industry was maintained. This condition is inseparable from government interference in the context of National Economic Recovery so that the financial performance of the Islamic banking was under threshold value. Modeling estimator using VAR at optimum lag 1 and showed that financial variable shock due to the Covid-19 Pandemic were responded to in the short term. The dynamics of variables and the recovery towards equilibrium conditions take varying amounts of time. The biggest contribution from the change in response results from the variable itself but the contribution weakens further and the dominant determinant variable to the change in response is the VARIABLE SIZE.